Analýza nákladů bytových domů - Opatovská, Lucia (Vysoké učení technické v Brně. Fakulta stavební, 2018)
Diplomová práca je vypracovaná na tému analýza nákladov bytových domov. Teoretická časť je zameraná na charakteristiku a vývoj stavebného a realitného trhu, popísanie developerských projektov a ich riadenie, ceny v stavebníctve a tiež rozpočty stavebných objektov. V praktickej časti analyzujem náklady konkrétneho developerského projektu. stanovujem cenu podľa rozpočtu, poukazujem na možnosti zníženia tejto ceny, zostavujem časopriestorové grafy a tiež finančné plány projektu.

The diploma thesis deals with the topic of housing cost analysis. The theoretical part of the thesis focuses on the characteristics and development of the construction and real estate market, the description of development projects and their management, the prices in the construction industry as well as the budgets of the buildings. In the practical part of the thesis, I analyze the costs of a particular development project. I set the price according to the budget, I point out possible ways of lowering this price, compiling time-charts and also the financial plans of the project.
29/5000 Cost analysis of the residential buildings
Keywords: analýza; náklady; developerský projekt; ceny; finančné plány; analysis; costs; development project; prices; financial plans